ACCOUNTABILITY OF PRIVATE UNIVERSITY TAX MANAGEMENT THROUGH THE IMPLEMENTATION OF GOOD UNIVERSITY GOVERNANCE PRINCIPLE - hambani, susi (JURNAL ILMIAH LIVING LAW, 2015)
The Implementation of Good University Governance Principles for private universities facing several obstacles in the term of tax accountability, regarding that private university is not the tax subject but the foundation as the organizer that become the subject to the tax. The establishment of private universities governed by Law No. 12 year 2012 on Higher Education, which is stated that private university is a college that established and / or organized by the society by establishing a legal organizing board as a non-profit legal entity, such as foundation. So, based on that regulation, the rule requires that private university does not stand alone as a legal entity, without a foundation as the organizing board.This study is a descriptive analysis research using normative juridical approach and Empirical Juridical Review. The results showed that the tax obligations of private universities are withhold, deposit and report taxes conducted on behalf of the founders of the foundation. Accountability requires that the university should be able to account for the whole process of implementation of the university to all stakeholders, both internal and external, especially in the general society.